6ER-002 A comparative review of the impact of the introduction of on-site molecular testing on the management of adult patients hospitalised with suspected influenza virus infection. (24th March 2020) - O'Connor, S; Schmid, M; Lyne, J; O'Meara, M; Kennedy, I; Zhangxiang, Y; Hickey, E; Mchugh, J; Scanlon, E; Creedon, G; Nolan, M
Abstract : Background and importance: Hospitalised influenza positive patients should be isolated and prescribed antiviral treatment. During the flu season of 2017–2018, influenza screens were processed off-site. On-site molecular flu testing was introduced prior to the 2018–2019 season. This study investigated its impact on the clinical management of hospitalised adult patients with a high suspicion of influenza virus infection. Aim and objectives: This retrospective cohort study investigated the impact of on-site influenza testing on adult inpatients by comparing key clinical parameters over the flu seasons before and after its introduction. Material and methods: Data from influenza peaks in January 2018 and January 2019 were used to compare: (i) uptake of influenza testing, using laboratory records; (ii) turnaround times (TATs), recorded using iLab; (iii) infection control isolation data; and (iv) oseltamivir use, as prescribed in inpatient drug kardexes. Results: Number of flu tests performed: 2018=47; 2019=73 (55% increase). Median TAT (days): 2018=7.2 (range 4–11); 2019=0.5 (range 0–3). Appropriate isolation of flu positive patients: 2018=36% (8/22); 2019=78.3% (18/23). Flu exposure (bed nights): 2018=48 (48/98, 49%); 2019=12 (12/110, 10%). Flu exposure in coronary care (no isolation facilities) (bed nights): 2018=7 (2 patients); 2019=10 (4 patients). Inappropriate isolation of flu negative patients (bed nights): 2018=41 (results unavailable during treatment); 2019=0. Appropriate oseltamivir use in flu positive patients: 2018=63.6% (14/22); 2019=95.7% (22/23). Oseltamivir use in flu negative patients: 2018=60% (15/25) and median duration=5 days (range 2–7); 2019=28% (14/50) and median duration=1 day (range 1–3 days). Appropriate isolation and oseltamivir use in flu positive patients: 2018=27% (6/22); 2019=74% (17/23). Conclusion and relevance: Increased flu screening in 2019 despite a national fall in hospitalised flu cases compared with 2018 suggests that clinicians were more likely to consider influenza when rapid diagnostics were available on-site. On-site testing significantly reduced TAT, having a measurable impact on the appropriateness of isolation and oseltamivir use. The absence of isolation facilities in the coronary care unit represented a significant clinical risk of influenza exposure. References and/or acknowledgements: No conflict of interest.